SMART SENSOR TELEVISION: ALAT PENDETEKSI JARAK PANDANG TELEVISI OTOMATIS SEBAGAI UPAYA MENJAGA KESEHATAN MATA - Purnomo, Arif; Widodo, Catur Edi; Perdana, Muhamad Iqbal; Fernando, Roy; Ariyanto, Yossy (Program Kreativitas Mahasiswa - Karsa Cipta, 2013)
Watching television with distance under five diagonal from the television make negative effects to eye lensâs health, that include myopia, photochemistry hurt, and astigmatism. Blue shine from the television could cause injury on eyeâs lens. According to Rahmi Utari from Mechanical R&D, the blue shine percentage in age among 0-10 years is 70-80%, meanwhile in age among 60-90 years is 20%. It means the radiation from blue shine can break the eyeâs lens in age among 0-10 years. Example, keep on watching distance from television. Watching television with position Â±250 will make neck injury, above 250 will tense neck and make headache also bucking. Smart Sensor Television is a tool to detect the automatically television visibility as effort to keep eyeâs health. Basically, the function of this tool is a health censorship of visibility in watching television. This tool has tree early warning such us LCDâs indicator, LEDâs indicator and buzzer soundâs indicator to know how far save distance to watching television. The procedure of this tool is when someone watching television with distance under five diagonal from television, the three indicators will give synergic response.